Primary School Students' Considerations In Electing Extracurriculars - Mukafa'ah, Anti Nur; Abduh, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
The purpose of the research carried out is to explore information about internal and external factors that influence student interest in the implementation of extracurricular activities at SDIT Muhammadiyah Al-Kautsar. The research method is qualitative on a case study approach. The subjects of this research included the head of student affairs and students of SDIT Muhammadiyah Al-Kautsar. Data collection using interview, documentation and observation techniques. The research carried out in this analysis technique uses the stages of collecting data, reducing data, presenting data, and drawing conclusions. The results of the study prove that the interest of students who take part in futsal extracurricular activities is higher than other extracurricular activities. The biggest internal factor influencing the selection of futsal extracurricular activities is aspiration, while the internal factor influencing the selection of archery extracurricular activities is motivation. The external factor that influences both is family in the form of support both in prayer, motivation and material.